NATIONAL INCOME IN AN ISLAMIC PERSPECTIVE - Fauzan Dwi Kusuma; Heni Noviarita; Tiondol Mayzal; Zein Adi Abung (Jurnal Signaling, 2023)
National income is an income received by the State against the production factor it runs in a certain period of time and if the national income of an area is high, the level of welfare will also be better. This research uses qualitative research methods that take data sources from various journals and websites. The purpose of this study is to find out the amount of state income, then to find out how national income can be beneficial for the welfare of the people. The results showed that the Ministry of Finance of the Republic of Indonesia reported the realization of state revenue reaching IDR 1,974.7 trillion until the end of September 2022. Meanwhile, the realization of state spending was recorded at IDR 1,913.9 trillion as of September 2022. This value grew by 5.9% (yoy) from the realization of spending in September 2021 of IDR 1,806.9 trillion. With a larger income compared to state spending, Indonesia has again scored a surplus in the state budget for the 9th time in 2022. The amount of state income will affect the welfare of the people. The government has made various efforts to make instruments to help the economy in the community, especially UMKM actors who are given additional capital.